SISTEM KEAMANAN DENGAN SENSOR PASSIVE INFRARED RECEIVER (PIR) DAN SOLENOID DOOR LOCK MENGGUNAKAN NODE MCU ESP8266 BERBASIS TELEGRAM - Wahyu Ibrahim; Nur Nawaningtyas Pusparini; Tupan Tri Muryono (EBID: Ekonomi Bisnis Digital, 2024)
Human needs for a more practical life are met by technological advances, one of which is in the health sector. This is the background of this research. By utilizing NodeMCU and Arduino Uno as microcontrollers for the IoT-based Smart Home system at the DKI Jakarta Health Office, it is hoped that the value of efficiency and security can be achieved through the implementation of an IoT-based Smart Home system. In this study, NodeMCU is used as a microcontroller in an IoT-based smart home system. Telegram Messenger is used in the design of this system as an input or notification medium. The chat input data is read out by the program for verification when the chat comes in. If verification fails, the system does not respond, and the chat input is reprogrammed. Conversely, if the lever is successful, the BOT will respond and send an input signal to the microcontroller to manage. After the microcontroller has processed the input signal, it will send an output signal (On/Off) to the relay, which will then send it to the output components (solenoid door lock, type sensor, and buzzer). take advantage of the technology that is already available by placing a Smart Home system that uses the Internet of Things. Since only those with certain access can control the home, such as viewing type sensors and unlocking doors remotely, IoT-based Smart Home systems are also secure.